Diseño y simulación de una antena de lente metálica en la banda ku para la optimización de un enlace satelital - Muyulema Yumiseba, Karla Elizabeth (2025)
This research project focuses on the design and analysis of a metallic lens intended for Ku-band. This lens is conformed by 3 layers: the first one is a lens of 3 short-circuited coplanar rings of 12 and 24 sectors, while the second and third layers are simple rings with a width of 15 mm (0.6λo) and inner diameters of 84 mm (3.36λo) and 100 mm (4λo), respectively. The proposed antenna is based on λ/2 and λ/4 resonators. In addition, the feeder is designed, which is a WR75 rectangular to square guide transition, in which a 40 mm inner diameter resonant ring and a 130 x 130 mm ground plane are placed. To achieve one of the objectives of designing the metallic lens operating in the Ku-band, the electromagnetic simulator CST Studio Suite is used. This software allows modeling and simulating the behavior of the antenna to achieve the desired performance in the band of interest, considering parameters such as gain, directivity, efficiency, reflection coefficient and radiation pattern. In addition, the plane wave incidence method is used to find the appropriate focal point to place the feeder with respect to the lens. The proposed lens is designed in 0.035 mm thick aluminum and has two models where the 12 and 24 sectors are merged, varying the separation between rings. For the feeder, aluminum is used throughout its structure. The results obtained from the electromagnetic simulator CST Studio Suite show that the proposed lens complies with the expected operating parameters. It is observed that there is an adaptation in the entire KU band below -10 dB for the reflection coefficient. In addition, there is a 7.4 dB increase in directivity around 12 GHz. Moreover, MATLAB Simulink, specifically the Satellite Communications toolbox, has been used to justify the lens performance. The scenario has been created and the antenna characteristics have been incorporated to observe and verify the link quality.